Managing the breeding herd - Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Successful swine producers pay careful attention to the breeding herd. The members of our producer panel will present three approaches to managing reproduction. Their ideas are of particular interest since each is a successful manager. This paper will serve as an outline of topics to be discussed. Basically the same problems occur in all common management systems; however, particular problems may be exaggerated under certain conditions. A well-known example is failure of gilts to reach puberty at an acceptable age. While some producers in all types of facilities experience this problem, complaints are considerably more frequent when gilts are bred in confinement. Because of confinement's negative effect, a good deal of research is in progress to determine what factors can influence puberty in gilts. Since the problem of delayed puberty also occurs in outside lots, this knowledge should be beneficial to all hog producers. Similarly, studying the way producers handle replacement gilts in different types of facilities should suggest ways of improving management under all circumstances.
Keywords: Swine; Breeding herd; Gilts; Sows; Boars